Developing Leadership Qualities of Young People in an Innovative Society - Komilova Fotimaxon Mahmudovna (International Journal on Integrated Education, 2022)
This article describes the need, opportunities and socio-psychological importance of preparing young people for leadership in the context of globalization, suggestions and recommendations for developing these qualities in young people in an innovative society.